Effect of Nandom’s Java Intelligent Tutor System on Computer Education Students’ Academic Achievement in Java programming Language in Universities in Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2025)
This study determined the effect of the Nandom’s Java Intelligent Tutor System (NJITS) on the academic achievement of students in Java programming language in Universities in south-east Nigeria. Population for the study is 136 students. Total population sampling technique was used. Data was collected using Java Programming Achievement Test (JPAT). The instrument was validated by five experts. Reliability index of 0.78 was established. After pretest, the experimental group was taught with NJITS and control group taught using lecture method. After the experiment, a posttest was given to both groups. Data collected were analyzed using Statistical Package for Social Science (SPSS). Mean and standard deviation were used to answer the research questions while Analysis of Covariance (ANCOVA) was used to test the null hypothesis formulated at 0.05 level of significance. Findings revealed that NJITS improved students’ academic achievement in Java programming language more than lecture method. Also, male students taught Java programming language using the NJITS had higher academic achievement than the female students taught Java programming language using the same tool.  A significant difference exists in the mean academic achievement scores of students of students, taught Java programming language using NJITS and those taught using the lecture method.